EVT Logistics Vehicle Cost Recovery Cycle and Economic Analysis. Issue 31 (2018) - Zeng, Xiaohua; Li, Hongcheng; Song, Dafeng; Yang, Nannan; Wang, Zhenwei
Abstract: Hybrid vehicles are favored by the market because of their good economic. Therefore, the cycle of cost recovery and its economy have become one of the most concerned issues in the development process. This paper analyzes the economic impact factors of logistics vehicles using electronic continuously variable transmission (EVT) hybrid power system. At the same time, the cost and the cost recovery cycle under different conditions were estimated and analyzed. Finally, the fuel economy of traditional vehicles, EVT logistics vehicle with electrified engine accessories and without electrified engine accessories was compared and analyzed. This paper provides a method for calculating the cost recovery cycle of hybrid vehicles. At the same time, it provides a reference for the development and design of the system from the perspective of obtaining better economical efficiency.